Social media addiction and social anxiety among UCSI University students in Kuala Lumpur - Mohamed, Malaahath; Syed Alwi, Syarifah Maisarah; Kahar, Rojanah (Global Academic Excellence (M) Sdn Bhd, 2024)
With the advancements of technological evolution, social media has become an essential part of our lives. There is a rising concern regarding university students’ dependence on social media use, which can lead to negative consequences for their emotional development, especially social anxiety and overall quality of life. This study cross-sectional study aimed to examine the relationship between social media addiction and social anxiety among private University Students in Kuala Lumpur. A total of 128 participants completed the Social Media Addiction Scale (SMAS) and the Social Interaction Anxiety Scale (SIAS). Data were analyzed using independent sample t-tests and Pearson’s correlation. About two-thirds (68.8%) of our students demonstrated a high level of social media addiction. 25 out of 128 participants exhibited a high level of social anxiety. Social media addiction was moderately correlated with social anxiety (r = 0.57**, p < 0.05). There was no significant gender difference in social media addiction and social anxiety. Rigorous validation of the findings by future studies is essential to understand better the effect of social media addiction and other possible factors on social anxiety.